2020
DOI: 10.1002/gcc.22889
|View full text |Cite
|
Sign up to set email alerts
|

Functional mechanisms of miR‐192 family in cancer

Abstract: By growing research on the mechanisms and functions of microRNAs (miRNAs, miRs), the role of these noncoding RNAs gained more attention in healthcare. Due to the remarkable regulatory role of miRNAs, any dysregulation in their expression causes cellular functional impairment. In recent years, it has become increasingly apparent that these small molecules contribute to development, cell differentiation, proliferation, apoptosis, and tumor growth. In many studies, the miR-192 family has been suggested as a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 135 publications
(206 reference statements)
0
11
0
Order By: Relevance
“…Our findings also revealed that circKIF5B plays a regulatory role by harboring miR-192 family members, miR-192, and miR-215 (not including miR-194). MiRNA-192 and miR-215 have been associated with promoting or suppressing tumors in various types of solid tumors (32)(33)(34)(35)(36). miR-215 was found to suppress papillary thyroid cancer metastasis by regulating the EMT via the AKT/GSK-3b/Snail signaling (37).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also revealed that circKIF5B plays a regulatory role by harboring miR-192 family members, miR-192, and miR-215 (not including miR-194). MiRNA-192 and miR-215 have been associated with promoting or suppressing tumors in various types of solid tumors (32)(33)(34)(35)(36). miR-215 was found to suppress papillary thyroid cancer metastasis by regulating the EMT via the AKT/GSK-3b/Snail signaling (37).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TRAF6 leads to increased production of type I IFN [ 54 ]. MicroRNAs (miRNAs) are small molecules that control gene regulation post-transcriptionally [ 92 ]. miR-146a has been shown to have a regulatory role in inflammation [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence has shown that miR-194-5p functioned as a tumor suppressor gene in cancers ( 29 ). Given miR-194-5p and its host gene highly expressed in GIT tissues, miR-194 may play a critical role in the tumorigenesis of GIC.…”
Section: Discussionmentioning
confidence: 99%